Composite membrane material as well as preparation method and application thereof
By using a composite membrane material with laminated nanofiber membrane and porous membrane, the problem of poor mechanical performance of existing porous polyurethane materials in strong oxidative or strong acidic environments is solved, and high strength, hardness, elasticity and chemical resistance are achieved, which are suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202410235216.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-01
- Publication Date
- 2025-04-04
AI Technical Summary
The existing porous polyurethane materials have poor mechanical properties under strong oxidative or strong acidic environments, and the pore structure and uniformity are difficult to control, which limits their application.
A composite membrane material is made of stacked nanofiber membranes and porous membranes. The nanofiber membrane is composed of interwoven nanofibers. The porous membrane has a sponge-like pore and/or finger-like pore structure, and the material is made of polyurethane or polyurethane prepolymer.
It realizes the high strength, hardness, elasticity and chemical resistance of composite film materials, and has strong controllability in process, and is suitable for a variety of application scenarios.
Smart Images

Figure CN119754045A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and in particular to composite membrane materials and preparation methods and applications thereof. Background Art
[0002] Porous polyurethane materials or porous polyurethane prepolymer materials have excellent mechanical properties and adjustable porous structures, and are widely used in various fields, such as buffer materials for protective plates, antibacterial materials in the biomedical field, sensors, thermal conductive structural adhesives, etc. However, due to problems such as the preparation process of porous membrane materials, their pore structure and uniformity are difficult to control, which affects the final mechanical properties in some strong oxidizing and strong acidic use environments, limiting their application. In addition, the morphology of porous materials in related technologies is relatively simple, and they cannot provide excellent comprehensive performance, which reduces their service life during application. Summary of the invention
[0003] In view of this, the embodiments of the present application provide a composite film material and a preparation method and application thereof. The preparation process of the composite film material is highly controllable, the structure of the composite film material can be flexibly adjusted, and it can have high strength, hardness, elasticity and chemical resistance.
[0004] A first aspect of an embodiment of the present application provides a composite membrane material, comprising a stacked nanofiber membrane and a porous membrane; the nanofiber membrane comprises interwoven nanofibers and has a pore structure; the pore structure in the porous membrane is sponge-like pores and / or finger-like pores; the materials of the nanofibers and the porous membrane independently include polyurethane or polyurethane prepolymer.
[0005] The nanofiber membrane is isotropic, and the risk of stress concentration points inside it is very small, and the uniformity is good, which can provide higher strength and hardness, as well as a certain elasticity; based on the inherent properties of polyurethane or polyurethane prepolymer and the specific pore structure morphology, the porous membrane can provide good elasticity as well as a certain strength, hardness and chemical resistance. Therefore, the composite membrane material provided in the embodiment of the present application has high strength, hardness and elasticity, and has a wide range of application scenarios.
[0006] The second aspect of the embodiment of the present application further provides a method for preparing a composite film material, which can be used to prepare the aforementioned composite film material provided in the embodiment of the present application. The preparation method comprises:
[0007] A casting liquid is applied to at least one side of the nanofiber membrane to obtain a prefabricated membrane with a casting layer; wherein the nanofiber membrane comprises interlaced nanofibers and has a pore structure, and the material of the nanofibers comprises polyurethane or polyurethane prepolymer; and the casting liquid is an organic solution containing polyurethane or polyurethane prepolymer;
[0008] The cast film layer is phase-converted to form a porous film with sponge-like pores and / or finger-like pores to obtain a composite film material.
[0009] Compared with the foaming process used in related technologies, the above preparation method is simple to operate, has stronger process controllability, shorter process time, and higher production efficiency; and it is easier to produce polyurethane or polyurethane prepolymer porous materials with good structural uniformity. The nanofiber membrane is used as a substrate to guide the formation of the porous membrane. The pore structure of the porous membrane is continuously adjustable, the production flexibility is high, and it is suitable for large-scale industrial production.
[0010] The third aspect of the embodiment of the present application provides a filtering device, including the composite membrane material provided in the first aspect of the embodiment of the present application, or including the composite membrane material prepared by the preparation method provided in the second aspect of the embodiment of the present application. Since the composite membrane material provided in the embodiment of the present application is used as a filtering component, the filtering device can have both a better filtering effect and a longer service life.
[0011] The fourth aspect of the embodiments of the present application provides a battery, comprising a positive electrode, a negative electrode, and a composite film material provided by the first aspect of the embodiments of the present application located between the positive electrode and the negative electrode, or comprising a positive electrode, a negative electrode, and a composite film material prepared by the preparation method provided by the second aspect of the embodiments of the present application located between the positive electrode and the negative electrode.
[0012] Due to the composite film material provided in the embodiment of the present application, the battery can exhibit higher structural stability during the charge and discharge cycle process. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1A is a scanning electron microscope (SEM) photograph of the nanofiber membrane prepared in Example 1;
[0014] Figure 1B is a SEM photograph of a cross section of a porous membrane of the composite membrane material prepared in Example 1;
[0015] Figure 2 is a SEM photograph of the nanofiber membrane of the composite membrane material of Example 1 after being immersed in a saturated potassium permanganate solution for 40 hours;
[0016] Figure 3 is a SEM photograph of the surface of the second porous membrane of the composite membrane material of Example 4;
[0017] Figure 4 is a SEM photograph of a cross section of a porous membrane of the composite membrane material of Example 2;
[0018] Figure 5 is a SEM photograph of a cross section of a porous membrane of the composite membrane material of Example 1;
[0019] Figure 6 This is a SEM photograph of the cross section of the composite material of Comparative Example 2. DETAILED DESCRIPTION
[0020] An embodiment of the present application provides a composite membrane material, comprising a stacked nanofiber membrane and a porous membrane; the nanofiber membrane comprises interwoven nanofibers and has a pore structure; the pore structure in the porous membrane is sponge-like pores and / or finger-like pores; the materials of the nanofibers and the porous membrane independently include polyurethane or polyurethane prepolymer.
[0021] The pore structure in the porous membrane is sponge-like pores and / or finger-like pores. It can be understood that sponge-like pores refer to: the cross-section obtained by cutting the composite membrane material with any plane, the morphology of the porous membrane is similar to the morphology of a sponge. Finger-like pores refer to: the pores in the porous membrane are finger-shaped on the cross-section obtained by cutting the composite membrane material with any plane parallel to the stacking direction of the porous membrane and the nanofiber membrane. In the embodiments of the present application, the porous membrane may have sponge-like pores alone, finger-like pores alone, or both finger-like pores and sponge-like pores. In the above-mentioned composite membrane material, the nanofiber membrane is isotropic, and the risk of stress concentration points inside it is very small, and the uniformity is good, which can provide higher strength and hardness, as well as a certain elasticity; based on the inherent properties of polyurethane or polyurethane prepolymer and the specific pore structure morphology, the porous membrane can provide better elasticity and a certain strength and hardness; in addition, polyurethane or polyurethane prepolymer has strong acid resistance, and the special pore structure makes the surface structure and pore structure of the composite membrane material become tighter when the composite membrane material is in a strong oxidizing environment for a long time, thereby further enhancing its mechanical properties. Therefore, the composite membrane material provided in the embodiment of the present application has high strength, hardness, elasticity and chemical resistance, and has a wide range of application scenarios.
[0022] Specifically, the above-mentioned composite membrane material can be used as a battery separator, and its superior mechanical properties can resist the internal osmotic pressure during the battery cycle, and based on the inherent properties of polyurethane or its prepolymer, the composite membrane material has strong chemical corrosion resistance and oxidation resistance. Therefore, its structural stability and chemical stability in the electrochemical device are both excellent, which is conducive to the performance of the electrochemical device. For another example, when a porous material is used as a filter material, when it has better mechanical properties, it is more conducive to extending its service life. Furthermore, the above-mentioned composite membrane material can also be used in any scenario with application value, such as thermal conductive structural adhesive, protective buffer material, polishing pad substrate, etc., and this application does not limit this.
[0023] In addition, the nanofiber membrane can also be used as a template to guide the formation of the porous membrane morphology, reduce the difficulty of preparing the porous membrane, improve the uniformity of the pore structure of the porous membrane, and improve the flexibility and accuracy of the pore structure regulation, which is conducive to its large-scale promotion and commercial application. It should be noted that the nanofiber membrane only guides the formation of the porous membrane morphology. Even if it is used as a template, the morphology of the porous membrane finally formed is completely different from that of the nanofiber membrane. Furthermore, the nanofiber membrane and the porous membrane of the above-mentioned composite membrane material both have a pore structure, especially the pore structure of the porous membrane can be used to accommodate other materials, for example, medical functional dressings, specifically medical antibacterial dressings, etc., so that the composite membrane material can be used in the field of biomedicine.
[0024] In some embodiments of the present application, the pore size of the sponge-like pores is 200nm-300nm. Specifically, the pore size of the sponge-like pores can be, but is not limited to, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm. Controlling the pore size of the sponge-like pores within the above range can improve the selectivity of the porous membrane and can take into account good mechanical properties. In the embodiments of the present application, the pore size of the sponge-like pores can be tested by SEM.
[0025] In some embodiments of the present application, at least some of the finger-shaped holes have sponge-like holes on at least some of the hole walls. The sponge-like holes on the hole walls have two advantages: first, they are conducive to sharing the pressure of filtration or penetration, thereby optimizing the comprehensive performance of the composite membrane material; second, they increase the specific surface area and porosity, which is conducive to subsequent filling, processing or direct use.
[0026] In some embodiments of the present application, the pore size of the finger-shaped pores is 2μm-5μm. In some specific embodiments, the pore size of the finger-shaped pores is 2μm-5μm, and the pore walls of the finger-shaped pores are distributed with sponge-like pores with a pore size of ≤300nm. In some specific embodiments, the pore size of the finger-shaped pores is 2μm-5μm, and the pore walls of the finger-shaped pores on the opposite side surfaces close to the porous membrane are distributed with sponge-like pores with a pore size of ≤300nm. Controlling the pore size of the finger-shaped pores within the above range while taking into account the sponge-like pores is beneficial for ensuring a faster liquid permeation rate while taking into account the strength of the porous membrane, and can also more evenly distribute the pressure of filtration or penetration. Furthermore, the pore size uniformity of the sponge-like pores on the pore walls of the finger-shaped pores is high. Specifically, any 4μm of the porous membrane 2 Within the area of the sponge-like pores, the pore size difference is ≤ 2. Specifically, the pore size difference refers to: any 4 μm of the porous membrane 2In the area, the pore with the largest pore size is a nm, and the pore with the smallest pore size is b nm, and the difference is the ratio of the largest pore size to the smallest pore size. Specifically, the pore size of the finger-like pores can be, but is not limited to, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5 μm; the pore size of the sponge-like pores can be, but is not limited to, 20 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 220 nmn, 250 nm, 280 nm, 300 nm.
[0027] In some embodiments of the present application, the pore structure of the porous membrane is sponge-like, and any 4 μm of the porous membrane 2 Within the area of the sponge-like pores, the pore size difference is ≤ 2. In this way, the uniformity of the porous membrane is good, which can improve the uniformity of the composite membrane material and ensure that the tensile strength of the composite membrane is high.
[0028] In some embodiments of the present application, porous membranes are provided on both sides of the nanofiber membrane. That is, the composite membrane material includes a first porous membrane, a nanofiber membrane, and a second porous membrane that are stacked. Among them, the pore structure of the first porous membrane can be the same as the pore structure of the second porous membrane, or it can be different. For example, the first porous membrane is a sponge-like pore structure, and the second porous membrane is a finger-like pore structure; or, the first porous membrane and the second porous membrane are both sponge-like pore structures or both are finger-like pore structures; it can also be that the first porous membrane is a sponge-like pore structure, the second porous membrane is a finger-like pore structure, and at least some of the finger-like pores have sponge-like pores on the pore walls of some areas. Those skilled in the art can make a choice according to actual production needs.
[0029] In some embodiments of the present application, the average diameter of the nanofibers in the nanofiber membrane is 100nm-300nm. In the embodiments of the present application, a scanning electron microscope (SEM) is used to measure the average diameter of the nanofibers. Specifically, the nanofiber membrane is observed under SEM. 2 The average value of the diameters of the nanofibers within the area. In this way, the isotropy of the nanofiber membrane can be improved, the loss of functional fillers or transmission profiles can be avoided during subsequent applications or processing, more fillers can be stored, and the fillers can be more evenly distributed or released. In some embodiments of the present application, the porosity of the nanofiber membrane is 50%-80%. In the embodiments of the present application, the wet method / immersion method can be used to evaluate the porosity of the porous membrane: water is allowed to infiltrate and fill the pores of the nanofiber membrane under pressurization or decompression, and the weight before and after is weighed to obtain the corresponding porosity ε=V 孔 / V膜外观 =V 孔 / (V 孔 +V 膜骨架 )=((m 湿 -m 干 ) / ρ 水 ) / ((m 湿 -m 干 ) / ρ 水 )+m 干 / ρ 聚氨酯 ). In the present embodiment, when calculating the porosity, ρ 聚氨酯 The value is 1.2g / cm 3 .
[0030] In the embodiments of the present application, the porosity of the porous membrane is not limited. Those skilled in the art can make a selection according to actual production needs and application needs. In some embodiments of the present application, the porosity of the porous membrane is 50%-80%. In some specific embodiments, the porosity of the composite membrane material is 50%-80%. In the embodiments of the present application, the porosity test of the porous membrane and the composite membrane material can refer to the test method of the porosity of the nanofiber membrane, which will not be repeated here.
[0031] In some embodiments of the present application, at least some of the holes in the porous membrane are connected to at least some of the holes in the nanofiber membrane. In this way, the liquid can more smoothly penetrate from the porous membrane to the nanofiber membrane, which is more conducive to its application. For example, when the composite membrane material is used as a filter material, it is conducive to improving the filtration efficiency. Further, when the two opposite sides of the nanofiber membrane are provided with porous membranes, it is more conducive to improving its uniformity while taking into account the mechanical properties of the composite membrane material, which is conducive to the performance of its performance.
[0032] In the embodiments of the present application, the above-mentioned polyurethane includes modified or unmodified polyurethane. Exemplarily, the modified polyurethane includes but is not limited to physically or chemically modified polyurethane. In the embodiments of the present application, the polyurethane prepolymer specifically refers to a reactive intermediate obtained by the reaction of polyols and isocyanates, and containing a carbamate group in the skeleton. The polyols and isocyanates provide the soft segment and hard segment of the polyurethane prepolymer, respectively. The polyurethane prepolymer can undergo a chain growth reaction with a low molecular weight compound containing active hydrogen to obtain a linear polyurethane (TPU) or a cross-linked polyurethane, which can be used to produce various polyurethane products.
[0033] In the embodiments of the present application, the materials of the nanofiber and the porous membrane may be the same or different. For example, the material of the nanofiber includes polyurethane, and the material of the porous membrane includes polyurethane prepolymer; for another example, the material of the nanofiber includes polyurethane, and the material of the porous membrane includes carbodiimide-modified polyurethane.
[0034] In order to further improve the mechanical properties of the composite membrane and extend its service life, in some embodiments of the present application, the material of the nanofiber and the porous membrane includes polyurethane. In some embodiments of the present application, the weight average molecular weight of the polyurethane is 8×10 4 -30×10 4 Controlling the weight average molecular weight of polyurethane within the above range can ensure that the mechanical properties and hardness of the composite film are high and make the composite film easy to prepare. Specifically, the weight average molecular weight of polyurethane can be but is not limited to 8×10 4 , 10×10 4 , 12×10 4 , 15×10 4 , 18×10 4 , 20×10 4 , 22×10 4 , 25×10 4 , 28×10 4 ,30×10 4 .
[0035] In order to further improve the mechanical properties of the composite membrane material, the nanofiber and / or porous membrane also includes a mechanical reinforcement material, which includes special engineering plastics and inorganic reinforcing fillers other than polyurethane, such as polysulfone, polyphenylene ether, polyphenylene sulfide, polyaryletherketone or at least one of carbon black, carbon nanotubes, ultrafine silica powder, and oxide nanoparticles. In some specific embodiments, in order to take into account the elasticity of the composite membrane material, the mass proportion of the mechanical reinforcement material in the nanofiber is controlled within the range of 0.1% to 1.5%. Similarly, in some specific embodiments, the mass proportion of the mechanical reinforcement material in the porous membrane is controlled within the range of 0.1% to 1.5%. Specifically, the mass proportion of the mechanical reinforcement material in the nanofiber membrane can be, but is not limited to, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%. Similarly, the mass proportion of the mechanical reinforcing material in the porous membrane can be but is not limited to 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, and 1.5%.
[0036] In some embodiments of the present application, the thickness of the nanofiber membrane is 30 μm-1300 μm. Controlling the thickness of the nanofiber membrane within the above range can, on the one hand, provide a substrate with sufficiently strong mechanical properties for the porous membrane, and on the other hand, in the preparation process of the composite membrane material, the nanofiber membrane can better play its guiding role, induce the formation of the porous membrane, and be more conducive to the regulation of the pore structure, thickness and other parameters of the porous membrane. Specifically, the thickness of the nanofiber membrane can be, but is not limited to, 30 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm, 1100 μm, 1200 μm, 1300 μm. In the examples of the present application, the thickness of the porous membrane is not limited, and those skilled in the art may select the thickness according to actual application requirements.
[0037] Accordingly, the present embodiment also provides a method for preparing a composite film material, which can be used to prepare the aforementioned composite film material provided in the present embodiment. The preparation method comprises:
[0038] S01, coating a casting liquid on at least one side of a nanofiber membrane to obtain a prefabricated membrane with a casting layer; wherein the nanofiber membrane comprises interwoven nanofibers and has a porous structure, and the material of the nanofibers comprises polyurethane or polyurethane prepolymer; and the casting liquid is an organic solution containing polyurethane or polyurethane prepolymer;
[0039] S02. causing the cast film layer to undergo phase transformation to form a porous film with sponge-like pores and / or finger-like pores, thereby obtaining a composite film material.
[0040] Compared with the foaming process used in related technologies, the above preparation method is simple to operate, has stronger process controllability, shorter process time, and higher production efficiency; and it is easier to produce polyurethane or polyurethane prepolymer porous materials with good structural uniformity. The nanofiber membrane is used as a substrate to guide the formation of the porous membrane. The pore structure of the porous membrane is continuously adjustable, the production flexibility is high, and it is suitable for large-scale industrial production.
[0041] In some embodiments of the present application, step S01 includes S11: preparing the nanofiber membrane by an electrospinning process, so that the nanofiber membrane can be guaranteed to have a high density under the premise of having a porous structure, which is conducive to the formation of a porous membrane and the mechanical properties of the final composite membrane. In some specific embodiments, the spinning solution containing the first raw material is electrospun to obtain the nanofiber membrane; wherein the first raw material includes polyurethane or polyurethane prepolymer, and the first raw material accounts for 8%-15% of the mass of the spinning solution. In this way, it is conducive to regulating the viscosity of the spinning solution within a suitable range, improving the spinnability of the spinning solution, and making the nanofiber membrane easy to prepare. Specifically, the first raw material can be, but is not limited to, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% of the mass of the spinning solution. In some specific embodiments, the room temperature viscosity of the spinning solution is ≤1000cP.
[0042] In the embodiments of the present application, room temperature refers to 25±3° C. The room temperature viscosity of the spinning solution can be tested by a rotational rheometer, and the test torque is between 30% and 60%.
[0043] In order to take into account the content of the first raw material in the spinning solution and improve the spinnability of the spinning solution, in some embodiments of the present application, the spinning solution also includes a viscosity reducer, which includes but is not limited to saturated fatty acids with carbon atoms of 8-14; for example, lauric acid, nonanoic acid, tetradecanoic acid, etc. The viscosity reducer is a small molecule substance, which as a small molecule will be inserted between the polyurethane or polyurethane prepolymer segments, and it will also remain in the final nanofiber. Therefore, in some embodiments of the present application, the nanofiber also contains a small amount of the aforementioned viscosity reducer. In order to avoid the viscosity reducer affecting the mechanical properties of the final nanofiber membrane, in some specific embodiments of the present application, the mass proportion of the viscosity reducer in the spinning solution is 1%-3%. Specifically, the mass proportion of the viscosity reducer in the spinning solution can be but is not limited to 1%, 1.5%, 2%, 2.5%, 3%. In some embodiments, the viscosity reducer is first added to the first solvent, stirred to dissolve it, and then the polyurethane or polyurethane prepolymer is added in batches.
[0044] In the embodiments of the present application, there is no restriction on the equipment used for electrospinning, which can be an electrospinning equipment commonly used in the field, for example, equipment equipped with a needle electrospinning launcher, equipment equipped with a disc-shaped electrospinning launcher. In the implementation of this application, there is no restriction on the process parameters in electrospinning, and those skilled in the art can choose according to production needs. In some specific embodiments of the present application, the conditions for electrospinning include: a voltage of 15-20KV, a distance between the transmitter and the receiver of the electrospinning equipment of 20 to 30cm, and a propulsion speed of the transmitter of 0.01mL / h-0.5mL / h. In this way, it is easier to obtain a nanofiber membrane with target parameters.
[0045] In some embodiments of the present application, step S11 further includes placing the material obtained by electrospinning in an oven for drying to remove the solvent (specifically the solvent in the spinning solution) to obtain the nanofiber membrane. Furthermore, before drying, the material is washed with deionized water.
[0046] In some specific embodiments, step S11 also includes high-temperature treatment of the material obtained after the above drying, so that the polyurethane or polyurethane prepolymer undergoes segment rearrangement, improves the regularity of its segment arrangement, and further improves the mechanical properties and hardness of the nanofiber membrane. Furthermore, it also includes trimming the uneven edges of the nanofiber membrane. In some specific embodiments, the temperature of the above high-temperature treatment is 150°C-180°C, and the duration is 3h-4h. Specifically, the temperature of the high-temperature treatment can be but is not limited to 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C.
[0047] In some embodiments of the present application, in step S11, the preparation of the spinning solution includes: adding polyurethane or polyurethane prepolymer to the first solvent, heating and stirring in a closed space; wherein the heating and stirring temperature is 40°C-70°C, and the stirring time is 1h-8h, to obtain a clear and transparent viscous spinning solution. In actual operation, polyurethane or polyurethane prepolymer can be added to the first solvent in batches. In some specific embodiments, step S11 also includes adding the aforementioned mechanical reinforcement material to the first solvent to improve the mechanical properties and hardness of the nanofiber membrane. That is, the spinning solution also includes a mechanical reinforcement material. It should be noted that even if a mechanical reinforcement material is added, the room temperature viscosity of the spinning solution needs to be controlled below 1000cP for spinnability.
[0048] In the embodiment of the present application, the first solvent is a good solvent for polyurethane or polyurethane prepolymer; for example, at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAC). In some specific embodiments, the first solvent includes NMP, and the mass of NMP accounts for less than 50% of the mass of the first solvent.
[0049] In some embodiments of the present application, in step S02, the preparation of the casting solution includes: adding polyurethane or polyurethane prepolymer to the second solvent, heating and stirring in a confined space; wherein the temperature of heating and stirring is 40°C-70°C, and the stirring time is 1h-8h, and a clear and transparent viscous spinning solution is obtained. At this time, the mass content of polyurethane or polyurethane prepolymer in the casting solution can be controlled to be 8%-15%, so that it is easy to form a casting layer and to proceed smoothly in the subsequent phase transformation process. Specifically, the second solvent includes at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAC). In some specific embodiments, the second solvent includes NMP, and the mass of NMP accounts for less than 50% of the mass of the second solvent. The second solvent and the first solvent may be the same or different. The above-mentioned second solvent is a good solvent for polyurethane and polyurethane prepolymer. Therefore, when the casting liquid is coated on the nanofiber membrane, the polyurethane or polyurethane prepolymer in the nanofibers on at least part of the surface of the nanofiber membrane is dissolved, so that in the final composite membrane material, the interface between the nanofiber membrane and the porous membrane is tightly connected, so that the risk of cracks or structural weaknesses at the interface of the composite membrane material during its application is extremely small, and the composite membrane material has high structural stability and a long service life.
[0050] In the examples of the present application, no viscosity reducer is required to be added to the casting solution. In some embodiments of the present application, the solid content of the casting solution is ≤35%. In this way, the porous membrane can be easily prepared.
[0051] In the embodiment of the present application, in step S02, there is no limitation on the coating method of the casting solution, as long as a flat and uniform casting layer can be formed. For example, a scraper can be used for coating.
[0052] In some embodiments of the present application, in step S02, causing the cast film layer to undergo phase transformation to form a porous film includes: S021, using an immersion phase transformation method, or, S022, using a steam-induced phase transformation method. That is, the preparation of the composite film material includes:
[0053] S01, coating a casting liquid on at least one side of the nanofiber membrane to obtain a prefabricated membrane with a casting layer;
[0054] S021. Using an immersion phase transformation method, the cast film layer undergoes phase transformation to form a porous film with sponge-like pores and / or finger-like pores, thereby obtaining a composite membrane material.
[0055] Alternatively, the method for preparing the composite film material comprises:
[0056] S01, coating a casting liquid on at least one side of the nanofiber membrane to obtain a prefabricated membrane with a casting layer;
[0057] S022. A steam-induced phase transformation method is used to cause a phase transformation of the cast film layer to form a porous film with sponge-like pores and / or finger-like pores to obtain a composite film material.
[0058] In some embodiments of the present application, step S021 uses an immersion phase transformation method to cause the cast film layer to undergo phase transformation, including:
[0059] The prefabricated membrane is placed in a coagulation bath; wherein the coagulation bath includes at least one of water, ethanol, methanol, isopropanol, n-butanol, isobutanol, isopropanol, n-heptane and n-hexane; or, the coagulation bath includes at least one of water, ethanol, methanol, isopropanol, n-butanol, isobutanol, isopropanol, n-heptane and n-hexane and a first solvent. Further, the mass content of the first solvent in the coagulation bath is controlled to be ≤15%. When the porous membrane is prepared by the immersion phase inversion method, the solvent exchange rate between the first solvent in the casting layer and the coagulation bath is fast, and it is easy to form a porous membrane with a more uniform pore structure. Specifically, in the actual operation process, the prefabricated membrane can be immediately placed in the coagulation bath after the casting layer is formed.
[0060] In some embodiments of the present application, step S022 uses a steam-induced phase transformation method to cause the cast film layer to undergo phase transformation, including:
[0061] The prefabricated membrane is placed in a constant humidity chamber and allowed to stand for a first period of time; the humidity of the constant humidity chamber is ≥70%, and the first period of time is ≥5 min. Specifically, there is no upper limit on the first period of time, but in order to improve production efficiency, the first period of time can be controlled within the range of 5 min-30 min. In some specific embodiments, the humidity of the constant humidity chamber is ≥85%, firstly, it is more suitable for factory equipment, and secondly, it can further improve the mechanical properties of the porous membrane. When the porous membrane is prepared by the immersion phase transformation method, the solvent exchange rate between the first solvent in the casting layer and the coagulation bath is relatively slow, which makes it easy to form a porous membrane with a more uniform pore structure.
[0062] In some embodiments of the present application, in step S022, the steam of the steam-induced phase inversion method includes but is not limited to at least one of water, ethanol, methanol, isopropanol, n-butanol, isobutanol, isopropanol, n-heptane and n-hexane; or, the coagulation bath includes at least one of water, ethanol, methanol, isopropanol, n-butanol, isobutanol, isopropanol, n-heptane and n-hexane and the first solvent.
[0063] In some embodiments of the present application, in step S022, the material obtained after the phase transformation is taken out from the constant humidity chamber and immersed in water to wash away the residual second solvent.
[0064] In the embodiments of the present application, when the steam-induced phase inversion method is used, the steam exchange rate between the casting film layer and the second solvent is low, and a porous film with sponge-like pores is more likely to be produced. When the immersion phase inversion method is used, the pore structure of the porous film is determined by the chemical potential difference between the casting liquid and the coagulation bath. For example, when the coagulation bath is one or a combination of polyurethane poor solvents with high polarity such as water and ethanol, a porous film with finger-like pores tends to be obtained; when the coagulation bath uses a reagent with low polarity, such as one or a combination of n-hexane, n-butanol, isobutanol, amyl alcohol, isopentanol, etc., a sponge-like pore structure tends to be obtained.
[0065] In some embodiments of the present application, after step S021 or S022, the material obtained after the phase conversion in step S021 or S022 is subjected to heat treatment at a temperature of 150°C-180°C and a heat treatment time of 5 min-4 h. Similarly, the polyurethane or polyurethane prepolymer can be rearranged to improve the regularity of its segment arrangement, thereby further improving the mechanical properties and hardness of the nanofiber membrane.
[0066] In some embodiments of the present application, the aforementioned mechanical reinforcement material is further added to the second solvent. In the embodiments of the present application, the viscosity of the casting solution is not limited, and a uniform casting layer can be formed.
[0067] For the convenience of description, the two opposite sides of the nanofiber membrane are defined as the first surface and the second surface. In some embodiments of the present application, when it is necessary to prepare a porous membrane on both the first surface and the second surface of the nanofiber membrane, a casting solution is first applied to the first surface, and a first porous membrane is formed on the first surface according to step S021 or S022, and then a casting solution is applied to the second surface, and step S021 or S022 is performed to form a second porous membrane. Further, in order to save process time, when the first porous membrane and the second porous membrane are prepared by the steam-induced phase inversion method, it includes:
[0068] The first surface of the nanofiber membrane is coated with a casting liquid to obtain a first pre-film, and the first pre-film is allowed to stand in a constant humidity chamber for a first period of time, and after being taken out, it is washed with water and then dried; after drying, the second surface of the nanofiber membrane is coated with a casting liquid to obtain a second pre-film, and the second pre-film is allowed to stand in a constant humidity chamber for a second period of time, and after being taken out, it is washed with water, and then dried and subjected to subsequent heat treatment. Similarly, whether to perform heat treatment can be selected as needed. Among them, the first casting liquid and the second casting liquid can be the same or different. For example, the solutes are different, the mass content of the solutes is different, etc.
[0069] In some other embodiments of the present application, the first porous membrane may be prepared by an immersion phase inversion method, and the second porous membrane may be prepared by a steam-induced phase inversion method. No further description is given here, and those skilled in the art may adapt according to actual production conditions.
[0070] The present application also provides a filtering device, including the composite membrane material provided in the present application, or the composite membrane material prepared by the preparation method provided in the present application. Since the composite membrane material provided in the present application is used as a filtering component, the filtering device can have both a better filtering effect and a longer service life.
[0071] An embodiment of the present application also provides a battery, comprising a positive electrode, a negative electrode, and a composite film material provided by the embodiment of the present application located between the positive electrode and the negative electrode, or comprising a positive electrode, a negative electrode, and a composite film material prepared by the preparation method provided by the embodiment of the present application located between the positive electrode and the negative electrode.
[0072] Due to the composite film material provided in the embodiment of the present application, the battery can exhibit higher structural stability during the charge and discharge cycle process.
[0073] The technical solution of the present application is further illustrated by multiple embodiments below.
[0074] Example 1
[0075] (1) heating the first solvent to 65° C., adding 100 g of a viscosity reducer (specifically lauric acid) to 8.5 kg of the first solvent (specifically DMF / NMP with a mass ratio of 1:1), and stirring for 5 min; then adding the first raw material (specifically TPU) in four portions, with a total amount of 1.5 kg of TPU, and stirring until a clear and transparent spinning solution is obtained;
[0076] The spinning solution was added to a needle electrospinning transmitter, 20KV DC high voltage electricity was applied, a flat and smooth aluminum foil was used as a receiver, the nozzle injection rate was 0.02mL / h, and the spinning was carried out for 3h; the power was turned off, the obtained material and aluminum foil were sent to a vacuum oven at 80℃ for 2h, and then the material was peeled off from the aluminum foil and sent to a 150℃ oven for heat treatment for 10min, and the thinner edges were cut off to obtain a flat nanofiber membrane.
[0077] (2) The second solvent was heated to 65° C., and the first raw material (specifically TPU) was added to 8.5 kg of the second solvent (specifically DMF / NMP with a mass ratio of 1:1) in four portions, with a total amount of TPU being 1.5 kg, and stirred until a clear and transparent casting solution was obtained.
[0078] The casting liquid is coated on one surface of the nanofiber membrane to obtain a prefabricated membrane with a casting layer. The prefabricated membrane is placed in a coagulation bath (specifically water) to allow the casting layer to undergo a phase transformation. The obtained material is rinsed with deionized water, dried at 100°C, and then heated at 150°C for 5 minutes to obtain a composite membrane material, in which the pore structure of the porous membrane is finger-like pores.
[0079] Example 2
[0080] (1) heating the first solvent to 60° C., adding 150 g of a viscosity reducer (specifically tetradecanoic acid) to 8.8 kg of the first solvent (specifically DMF / NMP with a mass ratio of 2:1), and stirring for 5 min; then adding the first raw material (specifically TPU) in four portions, with a total amount of 1.2 kg of TPU, and stirring until a clear and transparent spinning solution is obtained;
[0081] The spinning solution was added to a needle electrospinning transmitter, 15KV DC high voltage electricity was applied, a deionized horizontal plane was used as a receiver, the nozzle shooting rate was 0.5mL / h, and the spinning was carried out for 4h; the power was turned off, the obtained material and aluminum foil were sent to a vacuum oven at 80℃ for 2h, then heated to 100℃ for 2h, and sent to a 150℃ oven for heat treatment for 30min, and the thinner edges were cut off to obtain a flat nanofiber membrane.
[0082] (2) The second solvent was heated to 60° C., and the first raw material (specifically TPU) was added to 8.8 kg of the second solvent (specifically DMF / NMP with a mass ratio of 2:1) in four portions, with a total amount of TPU being 1.2 kg, and stirred until a clear and transparent casting solution was obtained.
[0083] The casting liquid is coated on one surface of the nanofiber membrane to obtain a prefabricated membrane with a casting layer. The prefabricated membrane is placed in a coagulation bath (specifically, n-butanol and isoamyl alcohol in a volume ratio of 1:1) to allow the casting layer to undergo a phase transformation. The obtained material is rinsed with deionized water, dried at 80°C, and then heated at 150°C for 5 minutes to obtain a composite membrane material, in which the pore structure of the porous membrane is sponge-like pores.
[0084] Example 3
[0085] (1) heating the first solvent to 70° C., adding 200 g of a viscosity reducer (specifically nonanoic acid) to 9.0 kg of the first solvent (specifically DMAC / DMF with a mass ratio of 1:2), and stirring for 5 min; then adding the first raw material (specifically TPU) in four portions, with a total amount of 1.0 kg of TPU, and stirring until a clear and transparent spinning solution is obtained;
[0086] The spinning solution was added to a disc-shaped electrospinning transmitter, 18KV DC high voltage electricity was applied, and a smooth surface of aluminum foil was used as a receiver. The nozzle injection rate was 0.05mL / h, and the spinning was carried out for 1h. Turn off the power, send the obtained material and aluminum foil to a vacuum oven at 80℃ for 2h, and then send them to a 150℃ oven for heat treatment for 10min, cut off the thinner edges, and obtain a flat nanofiber membrane.
[0087] (2) The second solvent was heated to 70° C., and the first raw material (specifically TPU) was added to 9.0 kg of the second solvent (specifically DMAC / DMF with a mass ratio of 1:2) in four portions, with a total amount of TPU of 1.0 kg, and stirred until a clear and transparent casting solution was obtained.
[0088] The casting liquid is coated on one surface of the nanofiber membrane to obtain a prefabricated membrane with a casting layer. The prefabricated membrane is placed in a coagulation bath (specifically DMF and n-butanol in a volume ratio of 1:10) to allow the casting layer to undergo a phase transformation. The obtained material is rinsed with deionized water, dried at 80°C, and then heated at 150°C for 5 minutes to obtain a composite membrane material, in which the pore structure of the porous membrane is sponge-like.
[0089] Example 4
[0090] The only difference from Example 1 is that step (2):
[0091] The second solvent was heated to 65° C., and the first raw material (specifically TPU) was added to 8.5 kg of the second solvent (specifically DMF / NMP with a mass ratio of 1:1) in four portions, with a total amount of TPU of 1.5 kg, and stirred until a clear and transparent casting solution was obtained.
[0092] The casting liquid is coated on the first surface of the nanofiber membrane to obtain a first prefabricated membrane with a casting layer, and the prefabricated membrane is placed in a coagulation bath (specifically, isoamyl alcohol and n-butanol in a volume ratio of 1:1) to allow the casting layer to undergo phase inversion, and the obtained material is rinsed with deionized water, dried at 80°C, and then heated at 150°C for 5 minutes after drying to obtain a composite membrane preform having a first porous membrane;
[0093] The above-mentioned casting liquid is coated on the side surface of the composite membrane preform away from the first porous membrane (the second surface of the nanofiber membrane), and the second prefabricated membrane with the second casting layer is placed in a constant humidity chamber with a humidity of 85% and allowed to stand for 10 minutes. After being taken out, it is immersed in deionized water for 10 minutes and rinsed, dried at 80°C, and then heated at 180°C for 5 minutes to obtain a composite membrane material, wherein the pore structure of the first porous membrane is sponge-like, and the pore structure of the second porous membrane is finger-like pores.
[0094] Example 5
[0095] The first solvent was heated to 65°C, PTMG 2000 (polytetramethylene glycol, molecular weight 2000, a conventional commercial material) was added to the first solvent and dispersed for 3 minutes to make it uniform, and then MDI 100 (diphenylmethane diisocyanate, a conventional commercial material) was added dropwise, and the ratio of isocyanate groups to hydroxyl groups in the system was 1.2, and the solid content of the reactants was 30%. The temperature was then raised to 80°C for reaction for 3 hours, and then the chain extender 1,4-butanediol was added, and stirred for 3 hours to obtain a clear and transparent spinning solution or casting solution. The remaining operations were the same as in Example 1 to obtain a composite membrane material.
[0096] Example 6
[0097] Step (1): The spinning solution is prepared in the same manner as in Example 1, and then 0.2 kg of polyethersulfone is added to the spinning solution. After heating and stirring until it is completely dissolved, electrospinning is performed. The spinning process differs from that in Example 1 in that the nozzle injection rate is 0.2 ml / h and the spinning time is 10 h.
[0098] Step (2): Heat the second solvent to 65°C, first add 0.2 kg of carbon nanotubes into 8 kg of the second solvent, stir for 24 hours under ultrasonic vibration to make them evenly dispersed in the solvent, then add 1.8 kg of TPU in four batches, after it is completely dissolved, quickly apply the casting liquid on one side of the nanofiber membrane and place it in water for 30 minutes. The subsequent washing and drying are the same as in Example 1, and the heat treatment time is increased to 3.5 hours to obtain a composite membrane material.
[0099] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.
[0100] Comparative Example 1
[0101] Comparative Example 1 is for preparing only a porous membrane layer. The casting liquid preparation process is the same as Example 1. The casting liquid is then coated on a flat and smooth glass plate and then placed in water for phase inversion. The subsequent rinsing and heat treatment processes are also the same as Example 1, and finally a porous membrane with finger-like pores is obtained.
[0102] Comparative Example 2
[0103] Comparative Example 2: A polyurethane nonwoven fabric was used as a substrate to prepare a porous membrane layer on the nonwoven fabric. The preparation process of the casting solution was the same as that of Example 1, and then the casting solution was coated on the polyurethane nonwoven fabric and placed in water for phase inversion to obtain a composite material.
[0104] Performance Testing
[0105] (1) Tensile property test: The tensile strength of the composite membrane material of each embodiment was tested using a universal tensile testing machine according to ASTM D638. The sample gauge length was 50 mm, the load loading speed was 5 mm / min, and the loading was continued until the sample was damaged. The tensile strength of each embodiment was obtained. The results are summarized in Table 3.
[0106] (2) Shore A hardness test: According to the rubber pocket durometer indentation hardness test method GB / T 531-1999, a Shore A durometer was used. The composite membrane material of each embodiment and the porous membrane of comparative example 1 were placed on a test platform, and a needle-type indenter was pressed into the material. The final hardness was obtained by reading the reading on the indicator. The results are summarized in Table 2.
[0107] (3) Resilience test: A dynamic thermal mechanical analyzer was used to test the resilience of the composite membranes of each embodiment and the porous membrane of comparative example 1. The static pressure was set to 5N. During the test, the temperature was increased from -40°C to 80°C. A curve of deformation and temperature was obtained. The deformation of the composite membranes was recorded when the temperature reached 75°C and when the temperature returned to room temperature at the end of the test. The deformation after returning to room temperature = (initial thickness - membrane thickness at room temperature after the test) / initial thickness. The results are summarized in Table 2.
[0108] (4) Micromorphology test: The micromorphology of the nanofiber membranes and composite membranes prepared in each embodiment and comparative examples 1-2 was tested by field emission scanning electron microscopy. For details, please refer to Figures 1A to 6 ; In addition, the average pore size of the porous membranes of the samples of Examples 1-6 and Comparative Example 1 was recorded, and the results are summarized in Table 1.
[0109] (5) Acid and alkali resistance and strong oxidation resistance test: The composite membrane materials of each embodiment and the porous membrane of comparative example 1 were cut into standard tensile specimens and immersed in an acidic solution of pH = 1, an alkaline solution of pH = 10, and a saturated potassium permanganate solution for 48 hours, respectively. After being taken out, the microscopic morphology and mechanical properties were detected.
[0110] (6) Porosity test: water is allowed to soak and fill the pores of the nanofiber membrane under pressure or decompression, and the weight before and after is measured to obtain the corresponding porosity ε = V 孔 / V 膜外观 =V 孔 / (V 孔 +V 膜骨架 )=((m 湿 -m 干 ) / ρ 水 ) / ((m 湿 -m 干 ) / ρ 水 )+m 干 / ρ 聚氨酯 ). In the present embodiment, when calculating the porosity, ρ 聚氨酯The value is 1.2g / cm 3
[0111] Table 1
[0112]
[0113] The average pore size of the first porous membrane in Example 4 is 350 nm, and the average pore size of the second porous membrane is 5000 nm.
[0114] Table 2
[0115]
[0116]
[0117] It should be noted that, for the composite membrane material of Example 4, the surface hardness of the nanofiber membrane is measured first, and then the composite membrane material is prepared. Among them, the surface hardness of the first porous membrane of Example 4 is 60HA, and the surface hardness of the second porous membrane is 45HA.
[0118] Table 3
[0119]
[0120] It should be noted that Figure 6 This is a cross-sectional photograph of the composite membrane material prepared in Comparative Example 2, and it can be seen that its structure is completely different from the porous membrane of the composite membrane material provided in the embodiment of the present application. Since non-woven fabric is used as the base material for film casting, the surface pores of the non-woven fabric are too large, and the casting liquid will penetrate into the interior of the non-woven fabric, making it difficult to form a separate film layer structure, and the structure of the porous membrane in the composite membrane material provided in the embodiment of the present application cannot be obtained at all. In addition, it can be seen from the data in Tables 1 to 3 that the composite membrane material provided in the embodiment of the present application has good structural uniformity, and has high surface hardness, tensile strength and elasticity, and its transverse tensile strength and longitudinal tensile strength are similar; at the same time, the composite membrane material provided in the embodiment of the present application has excellent chemical resistance.
[0121] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A composite membrane material, characterized in that: It comprises a stacked nanofiber membrane and a porous membrane; the nanofiber membrane comprises interwoven nanofibers and has a pore structure; the pore structure in the porous membrane is sponge-like pores and / or finger-like pores; the materials of the nanofibers and the porous membrane independently comprise polyurethane or polyurethane prepolymer.
2. The composite film material according to claim 1, characterized in that: The pore size of the sponge-like pores is 200nm-400nm; the pore size of the finger-like pores is 2μm-5μm.
3. The composite membrane material according to claim 1 or 2, characterized in that: At least some of the finger-shaped holes have sponge-like holes distributed on their walls.
4. The composite film material according to claim 1 or 2, characterized in that: The average diameter of the nanofibers is 100nm-300nm.
5. The composite film material according to any one of claims 1 to 4, characterized in that: The weight average molecular weight of the polyurethane is 8×10 4 -30×10 4 .
6. The composite film material according to any one of claims 1 to 5, characterized in that: The nanofiber and / or the porous membrane further comprises a mechanical reinforcement material, wherein the mechanical reinforcement material comprises at least one of polysulfone, polyphenylene ether, polyphenylene sulfide, polyaryletherketone, carbon black, carbon nanotube, graphene and nano-titanium dioxide; The mass proportion of the mechanical reinforcement material in the nanofibers is 0.1% to 1.5%; and / or, The mass proportion of the mechanical reinforcement material in the porous membrane is 0.1% to 1.5%.
7. The composite film material according to any one of claims 1 to 6, characterized in that: The thickness of the nanofiber membrane is 30 μm-1300 μm.
8. A method for preparing a composite membrane material, characterized in that: include: A casting liquid is applied to at least one side of the nanofiber membrane to obtain a prefabricated membrane with a casting layer; wherein the nanofiber membrane comprises interlaced nanofibers and has a pore structure, and the material of the nanofibers comprises polyurethane or polyurethane prepolymer; and the casting liquid is an organic solution containing polyurethane or polyurethane prepolymer; The cast film layer is phase-converted to form a porous film with sponge-like pores and / or finger-like pores to obtain a composite film material.
9. The preparation method according to claim 8, characterized in that: The preparation of the nanofiber membrane comprises: Electrospinning a spinning solution containing a first raw material to obtain the nanofiber membrane; wherein the first raw material includes polyurethane or polyurethane prepolymer, and the first raw material accounts for 8%-15% of the mass of the spinning solution; and the room temperature viscosity of the spinning solution is ≤1000 cP; The first raw material and the spinning solution further include a viscosity reducer, and the mass proportion of the viscosity reducer in the spinning solution is 1%-3%; the viscosity reducer includes a saturated fatty acid with 8-14 carbon atoms; The conditions for the electrospinning include: a voltage of 15-20 KV, a distance between a transmitter and a receiver of the electrospinning device of 20-30 cm, and a propulsion speed of the transmitter of 0.01-0.5 mL / h.
10. The preparation method according to claim 8, characterized in that: The solid content of the casting solution is ≤35%.
11. The preparation method according to any one of claims 8 to 10, characterized in that: The step of causing the cast film layer to undergo phase transformation comprises: Placing the prefabricated film in a coagulation bath, or placing the prefabricated film in a constant humidity chamber for a first period of time; Wherein, the coagulation bath comprises at least one of water, ethanol, methanol, isopropanol, n-butanol, isobutanol, isopropanol, n-heptane and n-hexane; or, the coagulation bath comprises at least one of water, ethanol, methanol, isopropanol, n-butanol, isobutanol, isopropanol, n-heptane and n-hexane and the solvent in the spinning solution; Alternatively, the humidity of the constant humidity chamber is ≥70%, and the first time duration is ≥5 min.
12. The preparation method according to any one of claims 8 to 11, characterized in that: After the phase transformation of the cast film layer, the method further comprises: heat treating the material obtained after the phase transformation, wherein the heat treatment temperature is 150° C.-180° C., and the heat treatment time is 5 min-4 h.
13. A filtering device, characterized in that: The invention comprises the composite film material as described in any one of claims 1 to 7, or comprises the composite film material obtained by the preparation method as described in any one of claims 8 to 12.
14. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode, and a composite film material as described in any one of claims 1 to 7 arranged between the positive electrode and the negative electrode, or a composite film material prepared by the preparation method as described in any one of claims 8 to 12.